Production of high‐titer transmission‐defective RNA virus‐based episomal vector using tangential flow filtration - Komatsu, Yumiko; Kakuya, Yoji; Tomonaga, Keizo (Microbiology and immunology, 2020)
In recent years, viral vector based in vivo gene delivery strategies have achieved a significant success in the treatment of genetic diseases. RNA virus‐based episomal vector lacking viral glycoprotein gene (ΔG‐REVec) is a nontransmissive gene delivery system that enables long‐term gene expression in a variety of cell types in vitro, yet in vivo gene delivery has not been successful due to the difficulty in producing high titer vector. The present study showed that tangential flow filtration (TFF) can be effectively employed to increase the titer of ΔG‐REVec. Concentration and diafiltration of ΔG‐REVec using TFF significantly increased its titer without loss of infectious activity. Importantly, intracranial administration of high titer vector enabled persistent transgene expression in rodent brain.